Temperature variation modeling for improving building HVAC control using built-in temperature sensors in smartphones - Wijukkana, Prach; Julsereewong, Amphawan; Thepmanee, Teerawat (My University, 2017)
Uniformity of temperature is important to comfortable indoor environment in building automation system (BAS). Usually, only a single temperature sensor is placed in the conditioned space for controlling an air handling unit (AHU) operation by using a direct digital controller (DDC) to maintain thermal comfort conditions. In order to improve an efficiency of heating, ventilating, and air conditioning (HVAC) control, a concept to integrate built-in temperature sensors in customers' smartphones into a traditional BAS for a multi-zone commercial building is introduced in this paper. Temperature variation modeling based on Monte Carlo simulation between the measured values from the primary temperature sensor and the built-in temperature sensors in smartphones in each zone is presented. Results obtained from the proposed modeling can be applied for multiple-sensor control strategy of HVAC system.
Keywords: BAS; commercial building; HVAC; modeling; Monte Carlo simulation; multi-sensor; temperature variation